Extremal Values of the Number of Inlets and Number of Bay Regions over Pericondensed Hexagonal Systems (2017)
In this paper we find extremal values of the number of inlets and the number of bay regions over PHSh, the set of pericondensed hexagonal systems with h hexagons. As an application, we determine extremal values of vertex-degree-based topological indices over PHSh.